2009
DOI: 10.1128/jcm.00312-09
|View full text |Cite
|
Sign up to set email alerts
|

emmand C-Repeat Region Molecular Typing of Beta-Hemolytic Streptococci in a Tropical Country: Implications for Vaccine Development

Abstract: We designed a study to investigate the molecular epidemiology of group A streptococcal (GAS) and group C and G streptococcal (GCS and GGS) disease in Fiji, a country which is known to have a high burden of streptococcal disease. Molecular typing of the N-terminal portion (emm typing) of the M protein was performed with 817 isolates (535 GAS and 282 GCS/GGS). We also performed genotyping of the C-repeat region in 769 of these isolates to identify J14 sequence types. The profile of emm types for Fiji was very di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 47 publications
4
39
1
1
Order By: Relevance
“…Although it appears from the present study that there is more diversity in emm types than previously reported, our findings are much less diverse than data from other countries, such as the United States (56 emm types), Bali (70 emm types), Fiji (52 emm types), and Ethiopia (76 emm types) (24)(25)(26)(27). In a recent study from Spain, 29 emm types and 45 emm subtypes were recognized (28).…”
Section: Discussioncontrasting
confidence: 55%
“…Although it appears from the present study that there is more diversity in emm types than previously reported, our findings are much less diverse than data from other countries, such as the United States (56 emm types), Bali (70 emm types), Fiji (52 emm types), and Ethiopia (76 emm types) (24)(25)(26)(27). In a recent study from Spain, 29 emm types and 45 emm subtypes were recognized (28).…”
Section: Discussioncontrasting
confidence: 55%
“…The variable nucleotide sequence encoding the N-terminal region of the M protein is not only the antigenic target for developing GAS vaccines (17)(18)(19) but also the basis for the sequence-based emm typing method (20). emm typing is the most widely used molecular typing approach, and more than 200 different emm types have been reported worldwide (21)(22)(23).…”
mentioning
confidence: 99%
“…The Results of both IFA and FACS ( Table 1) confirmed binding of JJo specific antibodies to the surface of GAS cells of diverse M types. All GAS strains typically contained within their last C-terminal repeat M-specific sequences corresponding to either J14 or J14.1 [18]. Anti-J14 antisera cross react with J14 and J14.1 and vice versa [19].…”
Section: Binding Characteristics Of Jjo Antibodies To Gas Isolatesmentioning
confidence: 99%